The Difference of Increment of Length and Weight Gain Between Infants Aged 2-6 Months Who Received Exclusive Breastfeeding and Those Who Received Non Exclusive Breastfeeding in Regional Primary Health Center in Pajang - Evi Kusumawati; . Widardo; Arsita Eka Prasetyawati (Nexus Kedokteran Komunitas, 2015)
Background: Breastfeeding patterns can affect the growth of infant. Exclusive breastfeeding can provide enough nutritions for infant growth until the age of 6 months. The purpose of the research was to know the difference of increment of length and weight gain between infants aged 2-6 months who received exclusive breastfeeding and those who received non exclusive breastfeeding in regional primary health center in Pajang. Methods: This was an analytic observational study with cross sectional approach, using simple random sampling technique. The number of the samples was 60 infants aged 2-6 months from some Posyandu (integrated health service units) in the neighborhood of regional Primary Health Center in Pajang in May-July 2014. Increment of length and weight gain data obtained by measuring the difference between current length and weight and those at birth then divided by infants age. Breastfeeding pattern was derived from the questionnaire. Data were analyzed using statistical test Mann Whitney and Independent t-test. Results: The test result for increment of length among infant aged 2-6 months who received exclusive breastfeeding and those who received non exclusive breastfeeding using a statistical test Mann Whitney showed the value of p=0,025. The test result for increment of weight gain among infant aged 2-6 months who received exclusive breastfeeding and non exclusive breastfeeding using Independent t-test showed the value of p=0,002. Conclusions: There is significant difference of increment of length between infants aged 2-6 months who received exclusive breastfeeding and those who received non exclusive breastfeeding in Regional Primary Health Center in Pajang and there is significant difference of increment of weight gain between infants aged 2-6 months who received exclusive breastfeeding and those who received non exclusive breastfeeding in Regional Primary Health Center in Pajang. Keywords: Increment of infant length, Infant weight gain, Exclusive breastfeeding, Non exclusive breastfeeding